Multimedia Interaktif Berbasis Web LUMIO by Smart sebagai Metode Alternatif dalam Meningkatkan Keterlibatan Santri pada Pembelajaran PAI - Noprianty, Anna; Jasiah (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2025)
Islamic boarding schools as traditional educational institutions have an important role in shaping the character of students, but challenges arise along with developments in technology and learning methods. This research aims to improve the quality of fiqh learning in class 10 MA Islamic Boarding School Manba'u Darissalam through the application of interactive media Lumio by Smart. This research uses a classroom action method which consists of the stages plan, act, observe, and reflect. Lumio media, especially the Super Sort activity, is used to make the learning process more interesting and interactive, even though Islamic boarding schools have a policy of prohibiting the use of gadgets. The research results show that using Lumio with the support of a projector and laptop can increase student involvement in the learning process, as well as facilitate understanding of fiqh material, especially about Hajj and Umrah. Lumio is proven to help teachers deliver material interactively through presentations and games, so that the quality of student learning increases.